Guidelines for creating crop-specific ontologies to annotate phenotypic data: version 2.2 - Pietragalla, Julian; Valette, Léo; Shrestha, Rosemary; Laporte, Marie-Angélique; Hazekamp, Tom; Arnaud, Elizabeth (Bioversity International and the International Center for Tropical Agriculture, 2024)
The Crop Ontology Guidelines version 2.2 provide detailed information and numerous examples for the use of the Trait Dictionary Template v.5.2 to develop a high quality Trait Dictionary with trait and variables used for the annotation of crop phenotypic data. The guidelines were developed in collaboration with the Integrated Breeding Platform and CIMMYT in the context of the CGIAR Big Data Platform.